Analysis of Motivation, Work Culture, and Work Environment on the Level of Employee Integrity in the Company - Okta KARNELI (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to analyze how motivation, work culture, and work environment will affect and give effect to the level of integrity of employees in a company. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data were obtained through library research techniques (library study) which refer to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of this study concluded that work motivation, work culture and work environment will greatly influence employee integrity. Motivation, work culture and work environment are one unit that must receive special attention for companies that wish to establish integrity in their employees.